Pendekatan Bermain Untuk Hasil Belajar Renang Gaya Bebas - Hasmarita, Sony; Husaeni, Ahmad (Jurnal Master Penjas & Olahraga, 2020)
The purpose of this study is to find out the impact of playing approaches on the results of free-style swimming studies on students of XII high school Mutiara 2 Bandung. This study is an experimental study. The subjects in this study are 25 students using total sampling techniques. The data collection technique used is a free-style swimming skill test. Research design used is One Group Pretes Postes Design. Based on the results of the research that has been obtained with data analysis and hypothesis testing, it can be concluded that there is a significant influence of money on the approach to play for the free swimming results of class XII students Mutiara 2 Bandung, because the score is higher than the table (22,624 > 17,108)